Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada Perusahaan Umum Daerah Air Minum (Perumda) Tirtayasa Kota Pekalongan - Tutut Dwi Andayani; Muhamad Yusuf; Alifia Shofiani; M Moegiri (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
The purpose of this study to examine the effects of the organizational size variables, personal technical skills, training and education programs, support from top management, and user involvement on the accounting information system performance simultaneously or in part. Purposive sampling was used in this study.This study had 50 respondents in its sample. The employees of the Tirtayasa Pekalongan Water Supply Company who had been working for more than a year in the counter/cashier, bookkeeping, cash, IT, engineering, PM and direct billing, customer data and accounts, CS, and marketing were the subjects of this study. This study utilized SPSS 27 for the multiple linear regression analysis method of data analysis.This study demonstrated that the performance of accounting information systems was significantly influenced simultaneously by organizational size, individual technical ability, training and education programs, support from top management, and user involvement. However, the performance of accounting information systems was influenced in part by the organization's size, individual technical ability, training and education programs, and support from top management. In the meantime, user involvement had no significant impact on accounting information system performance. Simultaneously the organizational size variables, personal technical skills, training and education programs, support from top management, and user involvement had significant effects on the accounting information system performance, and with a coefficient of determination or Adjusted R Square of 93,2%. Keywords: organizational size, personal technical ability, training and education programs, top management support, user involvement, accounting information system performance